Quadrant Interlocking Factorization Algorithm of Hourglass Matrix from Nonsingular Matrix: Olayiwola Babarinsa, Hailiza Kamarulhaili, Azfi Zaidi Mohammad Sofi - Team, Support (Thai Journal of Mathematics, 2021)
This paper presents the quadrant interlocking factorization (QIF) of nonsingular matrix, alternatively called WH factorization, to yield hourglass matrix (H-matrix). The WH factorization algorithm of H-matrix is synonymous to WZ factorization algorithm of Z-matrix, unlike LU factorization. We examine the conditions to generate the zero and nonzero entries of H-matrix from the factorization algorithm, and compare the H-matrix and Z-matrix. Then we conclude that the existence of WH factorization implies WZ factorization.